Początki naukowych badań nad bursztynem w Gdańsku i kolekcja Jacoba Theodora Kleina (1685–1759) - Sobecka, Anna (Artium Quaestiones, 2023)
The article deals with the collection of Jacob Theodor Klein and the beginnings of scientific interest in amber in early modern Gdańsk. The text is intended to show the importance of this forgotten collection and the ongoing research into succinite (Baltic amber). The objects from Klein’s collection themselves have been dispersed, and have not survived to the present day, but Klein’s written inventory, which in 1740 ended up in the collection in Bayreuth to later reach Erlangen, allows the collection to be analyzed thoroughly. It is the numerous drawings of amber exhibits that are of particular importance. Thanks to the activities of Klein and his contemporaries, including Johann Philipp Breyn, and the drawings made at their request by their daughters, it is possible to trace the flow of objects between collections and reconstruct the meaning of the ‘paper museums’ they created. The text points to the key role of illustration as an element of information exchange in the respublica litteraria of the time and collaboration of scholars. The role of Gdańsk collections as the basis for the great collections being created at the time in St Petersburg and Dresden is also highlighted.